Investigation of Locally Made Ceramic Filter for Household Water Treatment - Awaluddin Nurmiyanto; Agus Prasetya (Teknik Lingkungan Universitas Islam Indonesia, 2012)
This research have objective to develop and evaluate the performance of ceramic filter in using locally available material at Yogyakarta. Ceramic filter are made by pressing a mixture of clay, discarded pottery (grog) and combustible material (coconut fiber) into the molder. Curving processes are then applied to form tubular shape before firing it using kiln (1005°C). Filtration test were performed gravitationally by flowing well water into ceramic filter. Filtered water quality was complying with Indonesia drinking water quality standard (E.Coli and turbidity) although it has low filtration rate (0,461 L/Hr). The most optimum ceramic filter in turbidity and bacterial removal was composition number 10 clay+coconut fiber 4,5%(w/w)+grog 5%(w/w) that have average turbidity removal 88,2%, and average E. Coli removal 100%. N2 adsorption-desorption result on ceramic filter number 10 showed 0,04μm pore size, and 4,32m2/g pore surface area. The result from the XRD (X-ray diffractometer) indicates crystal structure of calcite and quartz on ceramic filter surface. Energy Dispersive X-ray (EDX) analysis showed Carbon compound as the most material constituent within the filter. Whereas micro’s photo using SEM (scanning electron microscopic) and TEM (transmitted electron microscopic) showed filter surface consists of stacked aggregates, separated by more randomly oriented particles.